A rare atypical chronic myeloid leukemia BCR-ABL1 negative with concomitant JAK2 V617F and SETBP1 mutations: a case report and literature review. (July 2020) - Gao, Tianqi; Yu, Changhui; Xia, Si; Liang, Ting; Gu, Xuekui; Liu, Zenghui
Atypical chronic myeloid leukemia (aCML) BCR-ABL1 negative is a rare myelodysplastic syndromes/myeloproliferative neoplasm (MDS/MPN) for which no standard treatment currently exists. The advent of next-generation sequencing has allowed our understanding of the molecular pathogenesis of aCML to be expanded and has made it possible for clinicians to more accurately differentiate aCML from similar MDS/MPN overlap syndrome and MPN counterparts, as MPN-associated driver mutations in JAK2, CALR, or MPL are typically absent in aCML. A 55-year old male with main complaints of weight loss and fatigue for more than half a year and night sweats for more than 2 months was admitted to our hospital. Further examination revealed increased white blood cells, splenomegaly, and grade 1 bone marrow fibrosis with JAK2 V617F, which supported a preliminary diagnosis of pre-primary marrow fibrosis. However, in addition to JAK2 V617F (51.00%), next-generation sequencing also detected SETBP1 D868N (46.00%), ASXL1 G645fs (36.09%), and SRSF2 P95_R102del (33.56%) mutations. According to the 2016 World Health Organization diagnostic criteria, the patient was ultimately diagnosed with rare aCML with concomitant JAK2 V617F and SETBP1 mutations. The patient received targeted therapy of ruxolitinib for 5 months and subsequently an additional four courses of combined hypomethylating therapy. The patient exhibited an optimal response, with decreased spleen volume by approximately 35% after therapy and improved symptom scores after therapy. In diagnosing primary bone marrow fibrosis, attention should be paid to the identification of MDS/MPN. In addition to basic cell morphology, mutational analysis using next-generation sequencing plays an increasingly important role in the differential diagnosis. aCML with concomitant JAK2 V617F and SETBP1 mutations has been rarely reported, and targeted therapy for mutated JAK2 may benefit patients, especially those not suitable recipients of hematopoietic stem cell transplants.